2009
DOI: 10.1590/s1807-59322009000900013
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Microcirculatory Dysfunctions and Translocation of Indigenous Bacteria in a Rat Model of Strangulated Small Bowel Obstruction

Abstract: PRUPOSE Bacterial translocation has been shown to occur in critically ill patients after extensive trauma, shock, sepsis, or thermal injury. The present study investigates mesenteric microcirculatory dysfunctions, the bacterial translocation phenomenon, and hemodynamic/metabolic disturbances in a rat model of intestinal obstruction and ischemia.METHODSAnesthetized (pentobarbital 50 mg/kg, i.p.) male Wistar rats (250–350 g) were submitted to intestinal obstruction or laparotomy without intestinal obstruction (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 53 publications
2
28
1
6
Order By: Relevance
“…However, we previously found positive correlations between the expression of P-selectin and intercellular molecules with leukocyte-endothelial interactions at the mesentery and lungs after hemorrhagic shock/reperfusion and sepsis. 7,19,24 And in the present study we found significant differences in leukocyte-endothelial interactions between the groups, which were not associated with hemodynamics. The increased leukocyte adhesion and migration to the perivascular tissue at the mesentery (distant locale) may have been induced by systemic inflammation biotrauma, which was prevented by low V T and attenuated by pentoxifylline.…”
Section: Limitationscontrasting
confidence: 44%
See 2 more Smart Citations
“…However, we previously found positive correlations between the expression of P-selectin and intercellular molecules with leukocyte-endothelial interactions at the mesentery and lungs after hemorrhagic shock/reperfusion and sepsis. 7,19,24 And in the present study we found significant differences in leukocyte-endothelial interactions between the groups, which were not associated with hemodynamics. The increased leukocyte adhesion and migration to the perivascular tissue at the mesentery (distant locale) may have been induced by systemic inflammation biotrauma, which was prevented by low V T and attenuated by pentoxifylline.…”
Section: Limitationscontrasting
confidence: 44%
“…However, leukocyte over-activation and increased leukocyte accumulation in the perivascular tissue can be associated with an exaggerated pro-inflammatory immune response that can contribute to widespread microvascular injury and consequent endothelial damage. 7,[24][25][26] Hypoperfusion of the gastrointestinal vascular bed has been suggested as a potential mechanism for the development of several complications from mechanical ventilation in critically ill patients. [8][9][10] We recently found that high intrathoracic pressure generated by high V T (10 mL/kg) and high PEEP (10 cm H 2 O) increased leukocyte-endothelial interactions in rat mesentery, as compared to PEEP values of 0 and 5 cm H 2 O, with no significant differences in mean arterial blood pressure between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As consequence, bacterial translocation and systemic inflammatory occur [7][8][9] . Zanoni et al 10 proposed a model modification, adding ischemia to intestinal obstruction, by ligature of terminal ileum blood vessels (7 to 10 cm of extension), promoting bacterial translocation and inflammatory response.…”
mentioning
confidence: 99%
“…O desencadeamento da sepse foi induzido por inoculação de bactérias vivas de E. coli obtidas de nódulos linfáticos mesentéricos em modelo de obstrução intestinal (Zanoni et al, 2009) (Trzeciak et al, 2007).…”
Section: Discussionunclassified